Geographical Storytelling: Towards Digital Landscapes in the Footsteps of Cuchlaine King - W. Brian Whalley (Geographies)
An information content approach is taken to producing a ‘digital description’ of a landscape utilising georeferencing within Digital Earth. A general view of the geomorphology of ‘northern England’ is used as a discussion area. Data points are geolocated using decimal latitude-longitude (dLL) that can be used as recording and search items in the literature, information landscapes, or ‘information fields’. Investigations, whether about landforms, events, sampling points, material properties, or dates, provide an ‘information set’ about geo-referenced points. Using the dLL format, such points also provide the basis for starts of transects and data points on topographic surfaces. The data sites provide an ‘information field’ about the area of interest and examples are given in the information landscape. The work of the late Cuchlaine King, physical geographer and geomorphologist, is used as examples of this information field approach by setting landforms and investigations into digitized physical landscapes. The paper also suggests ways of extending the information field idea to cover previous investigations and the possible implementation of Large Language Geographical Models in the employment of ‘big data’. The FAIR data principles of findability, accessibility, interoperability, and reusability are germane to the development of such models and their use.